Summary of the Results of Research and Selection of Corundum Crystalsfor Development and Creation of UV and VUV Detectors - Hovhannisyan, M. A.; Vardanyan, J. G.; Mnatsakanyan, A. R.; Mahtesyan, K. A.; Mkhitaryan, S. A.
The paper summarizes the results of our research conducted on the study of corundum crystals with various activating agents for development and creation of UV and VUV detectors. Corundum crystals with certain parameters were chosen as the optimal converter of UV and VUV radiant energy into the visible region of radiation for creating UV and VUV detectors with high spatial and temporal characteristics, which also have high radiation and thermal resistance.
Keywords: Physics